ANALISIS NERACA AIR DALAM PENENTUAN POTENSI MUSIM TANAM TANAMAN PANGAN DI PROVINSI BANTEN - Taufan Hidayat (Jurnal Floratek, 2006)
Analysis of Water Balance for Determine Growing Periods Potency of  Food Crops in Banten Province Taufan Hidayat, Yonny Koesmaryono, Aris Pramudia ABSTRACTGrowing periods can be determined using water balance analysis to decrease harvest risk in certain area. Generally, there are two types of land use for crop i.e. irrigated land and non-irrigated land. The experiment objectives was to determine growing periods of food crop inBantenProvince. Modified method of Thornthwaite and Mather of bookkeeping system of water balance was used based on decades data. Water balance analysis of irrigated land showed that  the area of Serang District had growing periods potencially of 140-170 days with growing periods starting from Dec2 till Jan1, but needed water supply from irrigation as amount 8.5-22.5 mm to grow rice twice a year or planted with other food crops after rice if no irrigation. Meanwhile, Tangerang District (Pakuhaji) and Pandeglang District (Pagelaran) had potency of 182-193 days of growing periods with starting on Sep3 at Pakuhaji and on Dec3 at Pagelaran. In these area rice could be planted twice a year without irrigation. Futher for non-irrigation land with monthly high rainfall, the result showed that the area had potency of growing periods of 182 days through the year. Planting dates might be started from October 1 until December 1, with sequence of rice-rice or rice-rice-other food crops.